Financial Performance of Dairy Cooveratives in West Java-Indonesia During the Covid-19 Pandemic and Foot-and-Mouth Disease Outbreak - Firman, Dr. Achmad; Mauludin, Mochamad Ali; Kusmayadi, Tendy (Buletin Peternakan, 2024)
Dairy cooperatives play an important role to collect milk production from dairy farmers, distribution of milk to the milk processing industry, concentrate supply services, credit guarantees, artificial insemination and animal health services, savings and loan services, and various other services carried out by cooperatives. This condition causes the dependence of dairy farmers on cooperatives to be quite high. External factors can influence cooperative resilience, such as the Covid-19 pandemic and Foot-and-Mouth Disease (FMD). Therefore, the purpose of this study was to analyze the performance of cooperative milk production, and to the financial performance of cooperatives in the post-pandem Covid-19 period and during FMD. The method used in this study was a survey method to KPBS Pangalengan which represents large cooperatives, KSU Tandangsari which represents medium-sized cooperatives, and KPS Bogor which represents small cooperatives. The analysis method used standard cooperative performance methods through regulations of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises (KUKM) of the Republic of Indonesia Number 06/Per/Dep.6/IV/2016 and key perfomance index to assess the financial performance of cooperatives. The results of the study showed that the performance of cooperative milk production decreased by 19.45% during the Covid-19 pandemic to the FMD as a result of the dairy cow mortality rate of 20.14%. The financial performance of dairy cow cooperatives was in the adequate category, both during the Covid-19 pandemic and FMD, but there was a decline in the ratio in all aspects of financial performance during the FMD. Thus, the performance of milk production and the financial performance of dairy cooperatives was better during the Covid-19 pandemic than during the FMD period. Therefore, strengthening milk production by providing new dairy cows and strengthening finances is very important